Are local crops home to frogs? A case study in the Ibiapaba Plateau, state of Ceará, Northeast Brazil - Tavares de Sousa Machado, Heitor; Araújo, Kássio de Castro; Silva de Oliveira, Samanta; Silva, Charles de Sousa; Waldemar Ávila, Robson (Herpetologia Brasileira, 2026)
Studies investigating the impact of agricultural landscapes on amphibian diversity are crucial to understanding their consequences on amphibian population dynamics. Nevertheless, some environments, such as montane ecosystems, are still understudied. Herein, we describe the anuran composition in several agricultural landscapes of the Ibiapaba Plateau, Ceará State, Northeast Brazil. We performed anuran sampling in January and February 2019, with a total sampling effort of 154 hours by 3 researchers in 29 collection days. We found 170 individuals in 20 species and six families, of which 65% were found in the National Park of Ubajara, Ceará, Brazil. The anuran fauna was similar regardless of the crop type, and the Hylidae and Leptodactylidae had the highest species richness and abundance. Overall, we observed that these crops are usually homes for generalist frogs that are more adapted to disturbed environments. This will support awareness of public policies aimed at herpetofaunal preservation and conservation in this mountain due to the increase of anthropogenic disturbances in these areas.